Competitive experience and performance status: an investigation into multidimensional anxiety and coping - Hanton, S.; Neil, R.; Mellalieu, S. D.; Fletcher, D. (European Journal of Sport Science, 2008)
In this study, we examined the influence of competitive experience (high vs. low) and performance status (current-elite vs. past-elite) upon athletes' (N=217) multidimensional trait anxiety, self-confidence, and coping responses. Significant interaction effects showed that the current-elite group, with high experience, had the highest levels of self-confidence and most facilitative interpretation of worry symptoms. Independent variable analysis revealed that the high-experience group reported lower somatic anxiety levels than their low-experience counterparts, and viewed the use of problem- and avoidance-focused coping strategies as more and less effective respectively. Current-elite performers reported lower worry intensity and more facilitative interpretations of somatic anxiety than the past-elite performers, as well as the use of more effective problem-focused and positive emotion-focused coping. The findings highlight competitive experience and performance status as important variables in the study of multidimensional anxiety and coping.